Application, knowledge and training needs regarding comprehensive geriatric assessment among geriatric practitioners in healthcare institutions: a cross-sectional study - Shanshan Shen; Xingkun Zeng; Xiaoliang Hui; Lingyan Chen; Jinmei Zhang; Xujiao Chen (BMC Geriatrics, 2024)
Abstract Background This study aimed to investigate the actual application, knowledge, and training needs of comprehensive geriatric assessment (CGA) among geriatric practitioners in China. Methods A total of 225 geriatric practitioners attending the geriatric medicine or geriatric nursing training were recruited for this cross-sectional study. The questionnaire included demographics, healthcare institution characteristics, the actual application, knowledge, training needs, and barriers to CGA and geriatric syndromes (GS). Results Physicians and nurses were 57.3% and 42.7%, respectively. 71.1% were female, with a median age was 35 years. Almost two-thirds (140/225) of geriatric practitioners reported exposure to CGA in their clinical practice. The top five CGA evaluation items currently used were malnutrition risk (49.8%), fall risk (49.8%), activity of daily living (48.0%), pain (44.4%), and cognitive function (42.7%). Median knowledge scores for the management procedures of GS ranged from 2 to 6. Physicians identified medical insurance payment issues (29.5%) and a lack of systematic specialist knowledge and technology (21.7%) as the two biggest barriers to practicing geriatrics. Nurses cited a lack of systematic specialist knowledge and technology (52.1%) as the primary barrier. In addition, physicians and nurses exhibited significant differences in their knowledge of CGA-specific evaluation items and management procedures for GS (all P < 0.05). However, there were no significant differences in their training needs, except for polypharmacy. Conclusions The rate of CGA application at the individual level, as well as the overall knowledge among geriatric practitioners, was not adequate. Geriatric education and continuous training should be tailored to address the specific roles of physicians and nurses, as well as the practical knowledge reserves, barriers, and training needs they face.